Attitudes of form two students towards learning science in English: a case study of schools in Kota Samarahan / Caesar Dealwis, Saira Joe and Sharifah Aishah Wan Kahar - Dealwis, Caesar; Joe, Saira; Wan Kahar, Sharifah Aishah (Universiti Teknologi MARA, Sarawak, 2005)
This paper presents the findings of a research project which examined the attitudes of Form Two students toward learning science in English. The research was both qualitative and quantitative and involved a total of 320 students from all the secondary schools in Kota Samarahan. The 3 objectives of this study were to determine the students' attitudes towards the English language, to determine the students' attitudes towards learning science in English and to determine if there was any significant relationship between attitudes towards the English language and attitudes towards learning science in English. The students had to complete one set of questionnaires which consisted of 40 items using a 5- point Likert Scale type. The data was analysed using SPSS version 12.0. There were 3 main findings of this study. Firstly, the findings showed that students with a good attitude toward English also had a positive attitude toward learning science in English. Secondly, female students had a more positive attitude towards learning science in English compared to the male students. Thirdly, there was no significant difference in the attitudes of the Malay and non- Malay students towards learning science in English.